Minutes of General Council (extract)
030-0078-001 G.C. 2 SEP. 1938 CONGRESS AGENDA. 2.9.38 The General Council continued to consider the Agenda of Congress. Resolution 48. Arms for Spain. Discussion took place on the addendum to Resolution No.48 from the Mineworkers' Federation of Great Britain, which read as follows:- "Congress also calls upon the General Council to organise immediately practical assistance -such assistance to be rendered by levies or any other means, as an obligation on affiliated societies to raise a sum equal to an amount of 2s.6d. per member". This was regarded as out of order and after discussion, Mr. Lawther expressed willingness to put the view to the Mineworkers' Federation Conference that the addendum be withdrawn and that the plea they were making to Congress should be put by their representatives when Paragraph 175 of the Report dealing with the Union's special efforts for relief in Spain was under discussion. Mr. Squance, whose Union was moving the resolution on arms for Spain, No. 48, said that he accepted that position. 292/946/30/78